Does patient knowledge affect the colorectal cancer risk in ulcerative colitis?. Issue 924 (1st October 2002) - Eaden, J A; Abrams, K; Mayberry, J F
Abstract : Objectives: Formal efforts to improve patient education are associated with fewer disease complications in a number of conditions. The possible relationship between knowledge about ulcerative colitis and its cancer risk, and the development of colorectal cancer using a previously developed and validated instrument—the Crohn's and colitis knowledge (CCKNOW) score—were investigated. Methods: The 24 item CCKNOW questionnaire was mailed to patients known to have developed colorectal cancer as a complication of ulcerative colitis (cases) and to colitics from the Leicestershire inflammatory bowel disease patient database who had not developed cancer (controls). Results: The mean (SD) CCKNOW scores for cases was 8.21 (3.02) and for controls was 8.27 (4.3). These scores did not differ significantly between cases and controls (difference 0.06, 95% confidence interval (CI) −1.7 to 1.5, p=0.9). There were four times as many members of the National Association of Crohn's and Colitis (NACC) in the control group compared with the cancer group and patients who are members of NACC achieve statistically significantly higher scores than non-members (11.6 v 7.8, p=0.05, 95% CI −0.1 to 7.6). However, after adjusting for NACC membership, the CCKNOW score did not appear to be associated with having developed cancer (odds ratio 1.04, 95% CI 0.92 to 1.18, p=0.5). Conclusions: The CCKNOW scores were comparable in cases and controls. Thus, in a retrospective study, no evidence has been demonstrated of an association between patient knowledge and the risk of developing colorectal cancer in patients with ulcerative colitis. However, knowledge may have been increased in cases as a direct result of having had colorectal cancer as a complication of ulcerative colitis.